Progressive collapse analysis of two existing steel buildings using a linear static procedure - JalaliLarijani, Reza; Çelikağ, Murude; Aghayan, Iman; Kazemi, Mahdi (Techno-Press, 2013)
In this study, the vulnerability of two existing asymmetric steel building frames to Progressive Collapse (PC) is assessed. The buildings have different frame systems, steel sections and number of stories (nine and six). An alternate path method (APM) with a linear static analysis (LS) is carried out according to General Services Administration (GSA) 2003 guidelines. The Demand Capacity Ratio (DCR) of each primary element (beams and columns) is given with its specific details for all frames. The results show that the nine-story building with a dual frame system (moment frame with bracing system) has a lower susceptibility and greater resistance to PC than the six-story building with a simple building frame system (gravity system with bracing system). Implementing built-up box-shaped sections for columns is a better choice than using built-up I-shaped sections because there is no weak axis for the box section.
Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: Linear Static Analysis (LS), Demand Capacity Ratio (DCR), deflection; Progressive Collapse (PC), ENGINEERING, CIVIL; MECHANICAL, Alternate Path Method (APM)